Dimensions of Audit Quality: Evidence From Eritrea - Tewelde, Hosie G.; Kiflemariam, Hewan; Berhe, Betiel Alem; Berhe, Ermias Tesfaldet; Adem, Adem Ibrahim (International Journal of Accounting and Financial Reporting, 2023)
Barely any research is presented concerning audit quality in Eritrea. Hence, as an icebreaker the aim of this paper is to investigate the fundamental audit quality factors and their impact on overall audit quality. Data on perception of audit quality was collected by a survey questionnaire including 41 audit variables from 119 audit clients. After categorizing the attributes into technical and functional sets, Factor Analysis was executed to identify the relevant factors. To further examine robustness and significance of the factors identified multiple regression was applied, after the data was tested for its assumptions. From the empirical results using Factor Analysis we documented four factors relating to technical audit quality and six factors associating with functional audit quality. We also justified the reliability and validity of the ten factors identified. Subsequently, the regression analysis depicted a positive and statistically significant relationship for all the ten technical and functional factors, except two. This supported our three hypotheses. With the consistent and higher rank of Eritrea on Corruption Perception Index, the originality and value of the findings can be potentially helpful to policy makers of control and audit, Eritrean audit firms and the body of knowledge in auditing concerning Eritrea.